A Study on the Relationship between Smart Factory Support Project and Corporate Productivity Improvement - Su Jin Kang, Man-Yong Han, Sang Cheol Lee (International Journal of Advanced Science and Technology, 2020)
Objectives: This paper studied on the effect of the introduction of smart factories. It examined whether there is a difference in productivity improvement according to smart factory level and industrial characteristics.